Carotid artery webs in embolic stroke of undetermined source with large intracranial vessel occlusion. Issue 4 (June 2021) - Labeyrie, Marc-Antoine; Serrano, Fabiola; Civelli, Vittorio; Jourdaine, Clément; Reiner, Peggy; Saint-Maurice, Jean-Pierre; Chabriat, Hugues; Houdart, Emmanuel
Background: Whether carotid artery web can be considered as a potential source of arterial thromboembolism in ischemic stroke remains uncertain. Aims: In a large sample of individuals with large intracranial artery occlusion, we compared the prevalence of carotid artery webs between patients with and without embolic stroke of undetermined source. Methods: In a single-center study of consecutive patients with anterior circulation ischemic stroke referred for mechanical thrombectomy, the presence of carotid artery web was systematically assessed by two independent readers. Thereafter, its prevalence was compared between patients with and without embolic stroke of undetermined source. Results: Among 466 patients of whom 12% were considered to have had an embolic stroke of undetermined source, ipsilateral carotid artery web was detected in 1.9% (confidence interval 95% = 0.7–3.1). Ipsilateral carotid artery web was more frequent in embolic stroke of undetermined source than in the rest of the sample (10.7% (confidence interval 95% = 2.7–18.7] vs. 0.7% (0–1.5), P  < 0.001). This difference remains significant after adjustment for sex, age, and vascular risk factor (odds ratio: 12.5 (2.1–72), P  = 0.005) or after exclusion of patients with any other bulb wall thickening ( P  = 0.025). In contrast, the difference of prevalence of contralateral carotid artery web between the two groups did not reach statistical significance (2.4% vs. 1.9%, P  = 0.6). Conclusions: Our results suggest that the presence of a carotid artery web might be considered as a potential source of large intracranial artery embolism. Longitudinal studies are needed to assess the exact risk of recurrence associated with these lesions.